BIRTH LENGTH AND FATHER'S EDUCATION RELATED TO STUNTING EVENTS IN TOLLS AGED 7-59 MONTHS - Yanuarti Petrika; Dahliansyah Dahliansyah; Ikawati Sulistyaningsih (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2023)
Chronic malnutrition experienced from childhood is the cause of stunting which is determined based on indicators of nutritional status of height according to age (TB/U). One of the factors causing stunting is the length of the child's birth body, and the father's level of education. This study sought to ascertain the association between father education and birth length and the prevalence of stunting in toddlers between the ages of 24-59 months. In the form of a cross sectional, this study used an analytical observational design. This study was conducted at five health centers in North Pontianak, namely Siantan Hilir Health Center, Siantan Hulu Health Center, Middle Siantan, Khatulistiwa Health Center and Telaga Biru Health Center with a sample of 384 toddlers aged 7-59 months who were selected by purposive sampling. Data on height measurement and determination of nutritional status were measured using a microtois device, while data on father's education and birth length were taken by conducting direct interviews with the respondent's mother using a questionnaire. Data on height and nutritional status of TB/U were analyzed descriptively, while to see the relationship between variables, chi-square analysis was used. Toddlers who have a history of short birth weight have more stunting nutritional status by 25.6%. Stunting and the history of the child's birth length were significantly correlated (p=0.019). Short-born infants are 2.29 times more likely to experience stunting as toddlers. The incidence of stunting is correlated (p = 0.033) with the educational level of fathers of children under five. Toddlers whose fathers have less education have 39.8% more normal nutritional status.